Integrating mHealth into adolescent sexual and reproductive health promotion in Nigeria: prospects and barriers - Ihesie, Chukwuemeka Austin; Chukwuogo, Ogoamaka (International Journal Of Community Medicine And Public Health, 2017)
Adolescent sexual and reproductive health (ASRH) is a key public health issue because of its impact on health and development. Adolescent SRH is linked to available information which often determines sexual behaviours. The use of mobile phones for health (mHealth) has shown success in delivering health education and behaviour change interventions for young people for smoking cessation, nutrition and in SRH. This article explores the possible prospects and barriers to the use of mHealth for ASRH promotion in Nigeria. This paper reviews secondary data from international and local literature obtained from database search. A conceptual framework and an applicability and transferability (A&T) tool guided the analysis of ASRH issues and feasibility of mHealth use in ASRH in Nigeria. The prospects of mHealth use for ASRH in Nigeria include the widespread coverage of mobile phone services and the acceptability of its use for health by Nigerian adolescents, unmet need in ASRH information provision and the similarity of some characteristics of Nigerian adolescents to other study populations where mHealth has been successfully used. Other prospects include the Nigerian government’s focus on ICT solutions and the availability of essential technical and organisational expertise for implementation. Possible barriers to the successful use of mHealth include poor funding for ASRH and inadequate information on implementation costs and cost-effectiveness which may make it difficult to present a business case. In conclusion, the use of mHealth in ASRH promotion in Nigeria is feasible and can be effective, however, measures must be taken to address specific barriers identified.